Odious debt law-and-economics perspectives - Bonilla, Stephania (Gabler, 2011)
The international debate on odious debt touches on many fundamental issues, including the intersection between ethics and finance, the moral responsibility of parties to international contracts and of sovereigns to their constituents. Stephania Bonilla analyzes the dynamics of sovereign debt relations and looks at how the incentive structures of the parties involved can have implications on odious debt. She specifically looks at the role of international law in the reputation mechanism sustaining creditor-debtor relations. Further, she examines the factors and players that drive change in sovereign debt governance, in an effort to move towards a more sustainable financial system with a more equitable distribution of burden between lenders and borrowers.